Soybean root system in function of soil compaction under no-tillage system - Cardoso, Eduardo Garcia; Zotarelli, Lincoln; Piccinin, Jorge Luiz; Torres, Eleno; Saraiva, Odilon Ferreira; Guimarães, Maria de Fátima (Pesquisa Agropecuaria Brasileira, 2006)
An experiment was carried out on a Rhodic Ferralsol, in Londrina, PR, to evaluate the soil compaction effects on soil morphostructure and on soybean root distribution, under no-tillage system. The field experiment was arranged in a completely randomized block (split plot) design with four replicates, and with the compacted treatments in the main plots and soybean varieties in subplots. The treatments were: one scarified soil until 20–25 cm depth layer with bulk density of 1.17 Mg m-3, and one compacted soil with bulk density of 1.38 Mg m-3, in a 12 cm depth. Two varieties of soybean, Embrapa-4 and BR-16, were cultivated on subplots. Roots developed in zones with less resistance of penetration and in biological tunnels. The soybean grain yield was not different under compacted and noncompacted soil, because soil water moisture was adequate. Embrapa-4 showed greater root density than BR-16.